Re-reading Dorothy Dinnerstein. Towards Dorothy Dinnerstein, The Mermaid and The Minotaur: Sexual Arrangements and Human Malaise: Препрочитувајќи ја Дороти Динерштајн. Кон Dorothy Dinnerstein, The Mermaid and The Minotaur: Sexual Arrangements and Human Malaise - Nikolovska, Ida (Identities: Journal for Politics, Gender and Culture, 2001)
Author(s): Ida Nikolovska | Ида Николовска Title (English): Re-reading Dorothy Dinnerstein. Towards Dorothy Dinnerstein, The Mermaid and The Minotaur: Sexual Arrangements and Human Malaise Title (Macedonian): Препрочитувајќи ја Дороти Динерштајн. Кон Dorothy Dinnerstein, The Mermaid and The Minotaur: Sexual Arrangements and Human Malaise Translated by (English to Macedonian): Ida Nikolovska | Ида Николовска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 257-259 Page Count: 3 Citation (English): Ida Nikolovska, “Re-reading Dorothy Dinnerstein. Towards Dorothy Dinnerstein, The Mermaid and the Minotaur: Sexual Arrangements and Human Malaise,” Identities: Journal for Politics, Gender and Culture, Vol. 1, No. 1 (Summer 2001): 257-259. Citation (Macedonian): Ида Николовска, „Препрочитувајќи ја Дороти Динерштајн. Кон Dorothy Dinnerstein, The Mermaid and the Minotaur: Sexual Arrangements and Human Malaise“, Идентитети: списание за политика, род и култура, т. 1, бр. 1 (лето 2001): 257-259.